Protecting Endangered Species (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The aim of this reprint is to immerse the reader in the latest studies on the conservation of endanger animals. The global biodiversity loss is a growing problem, and more species are becoming endangered and are at risk of extinction. Due to the development of human society, the space left for wildlife has become more limited. Therefore, saving endangered species and conserving biodiversity represent a matter of urgency. Due to the vulnerability of endangered animals and their sensitivity to environmental degradation and human disturbance, they need to be given more attention. Therefore, research on the conservation of endangered species has naturally become a hotspot in the field of ecology and conservation biology. Studies have shown that animals adapt to the ambient environment through their physiological regulation and behavioral strategies. Animals with strong ecological adaptability are able to resist uncertain changes in the environment. However, in the context of dramatic changes in the environment, the species that are less adaptable require more attention. In this reprint, we collected 18 papers that relate to the conservation of endangered and threatened animals. These papers cover some important aspects of endangered species conservation, such as ecological adaptation of animals, habitat alteration, climate change, population dynamics of endangered animals, conservation translocation, conservation genetics, pollution effect on animals, and construction of protected areas. We hope that this reprint will allow readers to understand the current trends in the conservation of endangered animals.